Alternative industrial development paths for Indonesia: SAM and CGE analyses - Bautista, Romeo M.; Robinson, Sherman; El-Said, Moataz (International Food Policy Research Institute, 1999)
In this article, we examine the economy-wide effects of three alternative growth paths for Indonesia's industrial sector using SAM (social accounting matrix) multiplier analysis and CGE (computable general equilibrium) modeling. The context of the analysis is the immediate post-crisis period — most likely to be in the next millennium — represented in our study by a modified benchmark data set for 1995. Special attention is given to the overall income and equity effects, considering that egalitarian growth has become a particularly important development objective in Indonesia. The results of SAM multiplier analysis indicate relatively strong macro-linkages from agricultural demand-led (ADL) industrialization, yielding a significantly larger increase in real GDP compared to that arising from industrial development oriented to either food processing or light manufacturing. The simulation results based on CGE modeling, which take account of nonlinearities and supply constraints that are ignored in SAM analysis, bear out the dominant influence of demand linkages in showing that ADL industrialization is associated with a larger GDP increase than the two industrial-led development paths.